Campos maduros com economicidade marginal: aspectos regulatórios - Távora, Patrícia Crichigno (2008)
This dissertation intents on showing how marginal and mature oil fields are important, both economically and socially in Brazil. These kind of fields were introduced on brazilian oil activities after Constitutional Amendment nº 9 (1995), that changed the way of exercising the monopoly on these activities. Mature and marginal oil fields have an essential characteristic: they operate on the limit of economic viability. That s why this dissertation proposes an specifc regulation to this kind of activity. As a matter of fact, this new scenario calls for new laws and regulations capable of offering incentives for the new players, like a royalty relief, sucessfully implemented in other countries, where the activities on marginal and mature oil fields are consolidated, like USA and Canadá